(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
This paper presents the indices of development for the selected dimensions of industry development in India. It provides details about the construction of composite indices in respective dimensions of industrial development. It explains the construct over five points of time covering the period 1971-2008. In addition dealing with the extent and pattern of inter-State disparities in the levels of development during this period provides a brief introduction to the respective dimension and justifies the selection of variables therein. Further, this study takes account of the trend in development levels, examines possibilities of absolute and conditional convergence and also determines the main sources of development at different points of time. The industrial dimensional indices are then used as input variables to the construct of a composite index of overall development.